2013
DOI: 10.1088/1748-0221/8/07/p07006
|View full text |Cite
|
Sign up to set email alerts
|

The use of mercury as a supplementary inner shielding material for low-background gamma-ray spectrometry

Abstract: Gamma-ray spectroscopic measurements of low-level environmental samples require the reduction of the background as low as practicable. In the present work, we investigate the advantages of adding Hg passive shielding inside a low-background Pb-shield to further reduce the background radiation. The background count rate achieved by the Pb-shield alone over the energy interval from 25 to 2700 keV, amounts to 8.4 × 10 −4 counts/s.keV which is ∼ 1.5% of the normal background. The introduction of Hg-shield adds ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In order to minimize the background radiation, the detector and the sample were housed in a cylindrical low-background Pb shield with 10 cm thickness (Canberra 747E). This shield was found to reduce the background in the gamma-ray spectra from 25 to 2700 keV by an attenuation factor of 98.5 % [21]. The whole experimental setup (detector and shields) was surrounded from the four sides with 2.5-cm borax and 3.5-cm paraffin wax.…”
Section: Methodsmentioning
confidence: 99%
“…In order to minimize the background radiation, the detector and the sample were housed in a cylindrical low-background Pb shield with 10 cm thickness (Canberra 747E). This shield was found to reduce the background in the gamma-ray spectra from 25 to 2700 keV by an attenuation factor of 98.5 % [21]. The whole experimental setup (detector and shields) was surrounded from the four sides with 2.5-cm borax and 3.5-cm paraffin wax.…”
Section: Methodsmentioning
confidence: 99%
“…Devore [4] utilized a light weight and high permeability material to form a truncated cone around a photomultiplier tube and improved its collection efficiency. Al-Sharkawy [8] added a Hg passive shielding inside a Pb-shield for the low-level gamma-ray spectrometers. Ren [9] found that the double-layer magnetic shield was theoretically as two times as that of the single-layer magnetic shield.…”
Section: Introductionmentioning
confidence: 99%